2013
DOI: 10.1016/j.ijhydene.2013.05.102
|View full text |Cite
|
Sign up to set email alerts
|

Poisoning-tolerant metal hydride materials and their application for hydrogen separation from CO2/CO containing gas mixtures

Abstract: Modibane, K.D. et al. (2013). Poisoning-tolerant metal hydride materials and their application for hydrogen separation from CO2/CO containing gas mixtures. AbstractMetal hydride materials offer attractive solutions in addressing problems associated with hydrogen separation and purification from waste flue gases. However, a challenging problem is the deterioration of hydrogen charging performances resulting from the surface chemical action of electrophilic gases. In this work, the feasibility study of poisonin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(26 citation statements)
references
References 22 publications
0
25
0
1
Order By: Relevance
“…Surface modification (fluorination, electroless deposition, etc.) of metal hydrides was applied to improve poisoning tolerance against CO and CO2 [30,31,[38][39][40]. Our research team [41] showed practical applicability of metal hydride technology for biohydrogen separation from different gas compositions.…”
Section: Metal Hydride System For Hydrogen Purificationmentioning
confidence: 92%
See 1 more Smart Citation
“…Surface modification (fluorination, electroless deposition, etc.) of metal hydrides was applied to improve poisoning tolerance against CO and CO2 [30,31,[38][39][40]. Our research team [41] showed practical applicability of metal hydride technology for biohydrogen separation from different gas compositions.…”
Section: Metal Hydride System For Hydrogen Purificationmentioning
confidence: 92%
“…Main disadvantage is low gravimetric density, which does not exceed 1 -2 %wt., but it is not significant limitation for stationary applications [12,17]. To current date, there are a number of practical application of metal hydrides in hydrogen storage systems [18][19][20][21], hydrogen compression [22-28], hydrogen purification [29][30][31].…”
Section: Metal Hydride Technologiesmentioning
confidence: 99%
“…27 More recently, it was found that the reaction rate is dependent on the surface structure and the electrolyte. 28,29 For the most common anode catalyst, platinum, the rate of hydrogen oxidation depends on the crystal orientation following the trend Pt (110)>Pt (100)>Pt (111). The Tafel reaction is the rate-limiting step in the case of Pt(110): 30,31 + ↔ − (Tafel reaction) (1)…”
Section: Mechanisms Of Co Poisoning 221 Electrochemical Reactions Imentioning
confidence: 99%
“…X-ray photoelectron spectroscopy results confirmed that the bond between Ni and CO was formed by a simple chemisorptions process, rather than forming nickel carbonyl. Modibane et al (2013) studied the deterioration of AB 5 type hydride in hydrogen purification from gases containing carbon dioxide (up to 30%) and monoxide (up to 100 ppm). The substrate La(Ni, Co Mn, Al) 5 was surface-modified by fluorination followed by electroless deposition of palladium.…”
Section: Metal Hydridesmentioning
confidence: 99%